WOODY PLANT DIVERSITY IN TROPICAL MOIST EVERGREEN CLOSED FOREST IN TAN PHU FOREST, DONG NAI PROVINCE - Manh Huong, Kieu; Duc Huy, Nguyen; Thi Danh Lam, Nguyen; Thi Luong, Nguyen; Van Hop, Nguyen (Journal of Forestry Science and Technology, 2021)
Plant diversity plays an important role in maintaining the protective and useful functions of the forest. This study aims to determine the diversity of woody plants as a basis for proposed solutions for the conservation of plant resources in the Tan Phu Forest, Dong Nai province. A total of 45 sample plots were divided equally into 3 forest states; Primer 6.1.6 and the SPSS 23 software were also used for the data analysis. The study showed that a total of 114 woody plant species of 89 genera belonging to 41 families were documented. There were 33 species (28.95%) were identified as threatened. Of these, 7 species were listed in Vietnam’s Red Data Book (2007), 3 species in Government Decree 06/2019, and 32 species in the IUCN Red List (2021). The number of ecologically significant species and ecologically dominant groups ranged from 19 to 20 species and 4 to 5 species, respectively. The diversity indices of Magarlef (d), Pielou (J’), Shannon-Weiner (H’), and Simpson (Cd) showing that the diversity of the woody plants was low. Most of the species analyzed (70.77 - 91.95%) had a regular distribution. Dalbergia cochinchinensis, Dalbergia oliveri, Knema pierrei, Aporosa microstachia; communities 17 and 43; and poor forest status was considered independently and unrelated to other species, communities, and states. It was also recommended that the suitable plot size for the list of woody species be greater than 45 plots. The results of this study provide a reliable scientific basis for the strategy for the management and conservation of forest resources, which helps to improve the use and effectiveness of the protective function of the forest in the study area.